Ab initio study of oxygen segregation in silicon grain boundaries: The role of strain and vacancies. (1st February 2021) - Maji, Rita; Luppi, Eleonora; Capron, Nathalie; Degoli, Elena
Graphical abstract: Abstract: Multi-crystalline silicon is widely used for producing low-cost and high-efficiency solar cells. During crystal growth and device fabrication, silicon solar cells contain grain boundaries (GBs) which are preferential segregation sites for atomic impurities such as oxygen atoms. GBs can induce charge carriers recombination significantly reducing carrier lifetimes and therefore they can be detrimental for Si device performance. We studied the correlation between structural, energetic and electronic properties of Σ 3{111} Si GB in the presence of vacancies, strain and multiple O segregation. The study of the structural and energetic properties of GBs in the presence of strain and vacancies gives an accurate description of the complex mechanisms that control the segregation of oxygen atoms. We analysed tensile and compressive strain and we obtained that local tensile strain around O impurities is very effective for segregation. We also studied the role of multiple O impurities in the presence of Si vacancies finding that the segregation is favorite for those structures which have restored tetrahedral covalent bonds. The presence of vacancies attract atomic impurities in order to restore the electronic stability: the interstitial impurity becomes substitutional. This analysis was the starting point to correlate the change of the electronic properties in Σ 3{111} Si GBs with O impurities in the presence of strain and vacancies. For each structure we analysed the density of states and its projection on atoms and states, the band gaps, the segregation energy and their correlation in order to characterise the nature of new energy levels. Actually, knowing the origin of defined electronic states would allow the optimization of materials in order to reduce non radiative electron-hole recombination avoiding charge and energy losses and therefore improving solar cell efficiency.